Multi-class polar lipid profiling in fresh and roasted hazelnut (Corylus avellana cultivar "Tonda di Giffoni") by LC-ESI/LTQOrbitrap/MS/MSn. (15th December 2018) - Napolitano, Assunta; Cerulli, Antonietta; Pizza, Cosimo; Piacente, Sonia
Highlights: An investigation of the polar lipids in hazelnut was reported. A LC-ESI/LTQOrbitrap/MS/MS n analytical method was developed. 120 polar lipids, from 5 classes were identified. Differences between fresh and roasted hazelnuts were determined. Abstract: Hazelnuts are a popular tree nut used whole or as an ingredient in a variety of bakery, candy and chocolate products. Based on the nutritional value and nutraceutical properties, mainly due to the lipid content, US Food and Drug Administration has recognized hazelnut as "heart-healthy" food. "Nocciola di Giffoni" is a Protected Geographical Indication (PGI) Italian hazelnut largely consumed but lacking of a comprehensive lipid profile. To acquire a detailed characterization of the polar lipids in fresh and roasted "Nocciola di Giffoni" hazelnut, an extensive analysis based on high-performance liquid chromatography coupled to multiple-stage linear ion-trap and orbitrap high-resolution mass spectrometry (LC-ESI/LTQOrbitrap/MS/MS n ) was carried out. This analytical approach (statistically validated) allowed for the detection of a wide range of polar lipids from oxylipins and long chain bases to high molecular weight lipids (phospholipids, sphingolipids, and glycolipids). Most of the polar lipids are here described for the first time in hazelnut.